The construction of religious identity in Palestine : an analysis of religious narratives - Arjan, Mohammed A.M (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This study aimed at investigating the religious narrative identity of the Palestinians by analyzing various forms of religious narratives of fourteen informants selected from the Palestinian middle class in the south of the West Bank (Hebron and Bethlehem cities). Theoretically, the study adopted a meta-theorizing approach by critically entering into a dialectical dialogue among various theories dealing with the narrative identity in general, and its implications for the religious identity in particular. This integrative approach covered Moral–ethical theories, Self-reflexivity theories, Autobiographical memory, Lived religion Paradigm and Islamic narrative sources. By employing the meta-theorizing strategy, the analysis was able to develop six themes regarding the religious narrative identity namely, unity of life, religious ethics, discursive narratives, practical ―embedded‖ narratives, trajectories narratives and religious experience narratives. These six themes were employed as guidance for analysis and initial orientation of the fieldwork. Methodologically, the study relied on the social life stories, and employed deductive and inductive strategies in its analysis. The main findings of the study, mainly in the first part of the analysis, focused on the social life stories of the informants and their emplotment over the life courses. The findings revealed that the informants attempted to emplot their turning points in order to find integrative narrative identity over the life courses while the centrality of religion in everyday lives was crucial in this integration. The second part of the analysis focuses on different major themes relating to religious narrative identity. In the unity of life theme, the findings manifested the centrality of religious concepts such as fiṭrah, religiosity, religious certainty, religious predestination and stability of religious involvements as main manifestations of the unity of Allah in emplotment of an intelligible narrative unity over the life course. Pertaining to discursive religious narratives, the findings showed that there are mutual disruptions between personal religious narrative and master religious narratives. The disruptions generate a sense of religious ontological insecurity and, consequently, shift toward religious transcendence as an alternative narrative. Regarding the religious practices, the findings demonstrated the centrality of various religious practices in configuration of informants' narrative identities in everyday life and the triumph of Islamic religious practice over folk religious beliefs. Regarding the religious experiences, the analysis disclosed three types of religious experiences: sacred places, religious contemplation, and religious dreams. The findings also found the significant role of the religious experiences in attestation of the unity of Allah and in enhancing religious identity among the informants. The analysis dialectically revealed that religious trajectories provoke religious experiences of the informants and religion contributes to emplotment of the social trajectories in positive ways. The findings further revealed that gender subject is presented in everyday lived religion. Finally, the study suggests a new lens for future research related to themes such as religious agency, relationships between the unity of life and unity of Allah.